Implementasi Peraturan Walikota Probolinggo Nomor 30 Tahun 2020 Tentang Sistem Akuntabilitas Kinerja Instansi Pemerintah (SAKIP): Studi Kasus Di Dinas Kesehatan, Pengendalian Penduduk Dan Keluarga Berencana Kota Probolinggo - Farasandya Amalia Hapsari; Dwi Ermayanti Susilo (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2023)
In the implementation of good, transparent, and accountable governance, several support systems are needed, one of which is the Government Agency Performance Accountability System (SAKIP) as stated in probolinggo Mayor Regulation Number 30 of 2020. This research was conducted to determine the implementation of Probolinggo Mayor Regulation Number 30 of 2020 concerning SAKIP at the Probolinggo City Health, Population Control and Family Planning Office in 2021. The method used is a qualitative approach by describing data and explaining data and using analytical techniques through data collection. The results of this study, that the implementation of Probolinggo Mayor Regulation Number 30 of 2020 concerning SAKIP at the Probolinggo City Health, Population Control and Family Planning Office in 2021 was not optimal, the ASN response was lacking and there was no influence whatsoever on the work performance of ASN. Therefore, it requires support, commitment and willingness from the leadership to utilize SAKIP as a medium of accountability and a media for management control by providing real rewards and punishments periodically to both the Regional Apparatus (PD) and the State Civil Apparatus (ASN).